Freeman's Syntactic Criterion for Linkage - David Hitchcock (Informal Logic, 2015)
Freeman’s syntactic criterion for linked argument structure (Freeman 2011) is often readily applicable, captures intuitively linked structures, and implies that refuting a single premiss of a linked argument suffices to refute the argument. But one cannot sharply separate analysis from inference evaluation in applying it, whether an argument satisfies it can be uncertain, it under-generates cases where refuting one premiss suffices to refute an argument, some arguments satisfying it can be easily rescued if a single premiss is refuted, and Freeman’s underlying account of probative relevance is dubious.